Young Yakuza - Limosin, Jean-Pierre (Celluloid Dreams, 2007)
Verzio FF Submission In an era where juvenile delinquency in Japan has hit an all-time high, the director tells the tale of an aimless twenty year-old who is faced with the choice of walking two distinctly different paths in life. Naoki has proven himself a miserable failure at both school and life; unemployable and socially incapable, the shiftless young man soon decides to make a name for himself in the Japanese underworld. Now, despite his mother's objections, Naoki leaves home for a year’s apprenticeship in the Japanese Mafia. Over the course of the next twelve months, the young man who could never find his way in life will be forced to choose between devoting himself to a life of crime, and struggling to remain righteous in a world consumed by selfishness and greed.